2020
DOI: 10.1111/resp.13881
|View full text |Cite
|
Sign up to set email alerts
|

Pleural effusions and pneumothorax: Beyond simple plumbing

Abstract: Pleural diseases affect millions of people worldwide. Pleural infection, malignant pleural diseases and pneumothorax are common clinical challenges. A large number of recent clinical trials have provided an evidence‐based platform to evaluate conventional and novel methods to drain pleural effusions/air which reduce morbidity and unnecessary interventions. These successes have generated significant enthusiasm and raised the profile of pleural medicine as a new subspecialty. The ultimate goal of pleural researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Several factors may be associated with treatment outcome including the rate of intrapleural inactivation of a fibrinolytic, levels of endogenous plasminogen, a higher level of active PAI-1 and extracellular DNA, and potentially the formation of biofilms (21). These may collectively, or synergistically contribute to poor outcomes in pleural infection (22).…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may be associated with treatment outcome including the rate of intrapleural inactivation of a fibrinolytic, levels of endogenous plasminogen, a higher level of active PAI-1 and extracellular DNA, and potentially the formation of biofilms (21). These may collectively, or synergistically contribute to poor outcomes in pleural infection (22).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that bacteria can thrive in both pleural fluid and pleural tissue (Popowicz et al, 2017). However, the invading mechanisms of microorganisms in the pleural cavity and features of the pathogenesis, such as the role of biofilm formation, have not yet been fully understood (Thomas et al, 2020). A recent study had reported that P. aeruginosa can form biofilm in an empyema model (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%